The Virgin of Luján: sacred source of legitimation of the heroes of the Malvinas War - Laura Marina Panizo (Cuadernos de Antropología Social, 2013)
The loss of a loved one in war, as in the extraordinary losses in general, produces a break in the usual ways of facing death. In this article we will see how relatives of fallen in the Malvinas War were adapted to these changes in a creative way, reformulating conventional models to understand them, through a framework of interpretation of losses where the Virgin of Luján, sacred source of legitimation of the dead and the bereaved, becomes the instrument through which occurs the communion of all Argentineans, both living and dead, and strengthening the national identity.